(untitled) (Global Journal of Human-Social Science, 2015)
The present study was conducted on 140 learning disabled students from elementary classes ( 6,7,and 8). Sample was taken from rural and urban schools of Shimla district of Himachal Pradesh. A self constructed scale on guidance needs was employed to measure the educational guidance needs of the students. Results showed that all the students possessed average level of educational guidance needs. Students did not vary in their educational guidance needs.